Prospective short‐term feasibility study of perioperative suprapubic catheters in laparoscopic colectomy. Issue 1 (16th May 2018) - Nagao, Sayaka; Saida, Yoshihisa; Enomoto, Toshiyuki; Takahashi, Asako; Higuchi, Tadashi; Moriyama, Hodaka; Niituma, Toru; Watanabe, Manabu; Asai, Koji; Kusachi, Shinya
Abstract: Introduction: Here we report a prospective study on whether a temporary suprapubic catheter (SPC) can be safely inserted as a substitute for transurethral balloon catheterization during laparoscopy‐assisted colectomy. Methods: Our subjects included 52 cases who gave informed consent to have an SPC inserted. These subjects were selected from cases who underwent laparoscopy‐assisted surgery for primary colorectal cancer from October 2014 to August 2015. Results: An SPC was inserted into 45 of the original 52 cases. The median surgical duration was 220 min (range, 11–438 min), and the SPC insertion was performed at a median of 133 min (range, 9–384 min) after the start of surgery. Insertion required a median duration of 116 s. In one case (2.2%), the bladder was perforated by the paracentesis needle, and in two cases (4.4%), hematuria was observed at the time of insertion; however, surgery was completed without any incident in these three cases. Six of the remaining 42 cases (13.3%) demonstrated neither micturition desire nor independent urination on the day the catheter was clamped. In these cases, the clamp was released two to four times, and draining of an average of 586‐mL urine, micturition desire, and independent urination were confirmed 2–4 days later. Conclusion: Transurethral balloon catheterization is a simple procedure that is commonly used on surgical patients, but it can cause pain, discomfort, and infection. In contrast, SPC insertion is a procedure that avoids crossing the urethra and its associated disadvantages. Here we were able to demonstrate that the procedure can be safely used in laparoscopic surgery patients.